Use, Perceptions and Attitudes of Cognitive and Sports Performance Enhancing Substances Among University Students - Constantinou, Demitri; Aguiyi, Ivan (Frontiers in Sports and Active Living, 2022)
The use of prohibited performance enhancing substances (PESs) is well-documented among athletes, and includes student athletes in institutions of higher learning. In addition to using PESs to enhance sporting performance, they may be used for cognitive and academic achievement, specifically through the use of neuroactive substances. The latter in particular is under-researched and poses public health risks. Understanding the extent and reasons for using or not using PESs by university students will assist in addressing further research, and means to deter their use. This study aimed to explore the prevalence, attitude, and perceptions of the use of both sport and academic performance-enhancing substances by students at two universities in Johannesburg, South Africa. The study utilized a cross-sectional, descriptive survey design using a self-administered online questionnaire. All registered students were invited to participate via email using the university communications modes, with a link to a Google Forms questionnaire. Ethical approval was granted for the study and data were collected anonymously. The sample size of responses with completed data was 548, comprising predominantly female and undergraduate students, with 32 (6%) indicating current or past use of PESs. Among the prohibited substances used, neuroactive drugs were mostly used, with cannabis the highest followed by stimulants. The most popular reasons reported were for academic and cognitive performance. Most responded with what would be deemed ethically appropriate answers on the perception of PES use and 72% of the participants believe that a drug-testing program will prevent their use in the university, and further, that educational programs will help improve students' knowledge of PES. Although relatively low usage, university students use performance enhancing substances, mostly for cognitive enhancement using neuroactive stimulants. Most believe that the use of all forms of PESs is high among their peers; and favor education and testing programs, suggesting that intervention programs may be effective. Better defined research should be conducted to unpack the broad findings in this study.